Impact of Covid-19 Pandemic on General Surgical Services at Karnali Academy of Health Sciences - Devkota, Harihar; Menyangbo, Suryaman; Khanal, Sushila; Rawal, Mangal (Journal of Karnali Academy of Health Sciences, 2020)
Background: Covid-19 pandemic that started from Wuhan China in 2019 December has made serious impact in the general wellbeing of people as well as the services provide by the health care institutions all over the world. This study aims to identify the impact of Covid-19 in the general surgical services provided by Karnali Academy of Health Sciences.Methodology: This was a descriptive observational study conducted at Karnali Academy of Health Sciences (KAHS), Jumla from 16th September 2019 to 15th September 2020 AD. The data were obtained from records of various departments concerned with the delivery of the surgical services at the Hospital, which were then extracted to the Microsoft Excel and analyzed.Results: Total 5,678 patients received general surgical services and the number of cases in each services remains somewhat consistent before lockdown however they tend to vary after lockdown. The average OPD cases decreased from 373 to 223 after lockdown and average surgeries performed were considerably decreased from 64 to 28. The average emergency services per month (160 vs. 189) and ICU admission (4 vs. 9) showed increment, however ward admissions (48 vs. 45) were fairly constant. The elective surgeries decreased considerably reaching to Zero during Apr/May and May/June periods. Conclusion: Surgical emergencies and ICU surgical services have not been decreased in KAHS although OPD and surgical procedures were decreased during COVID-19 pandemic in order to retain essential services as well as minimize risk of Covid-19 transmission.